2016
DOI: 10.1002/2016gl068956
|View full text |Cite
|
Sign up to set email alerts
|

New insights into gully formation on Mars: Constraints from composition as seen by MRO/CRISM

Abstract: Over 100 Martian gully sites were analyzed using orbital data collected by the Compact Reconnaissance Imaging Spectrometer for Mars (CRISM) and High Resolution Imaging Science Experiment on the Mars Reconnaissance Orbiter (MRO). Most gullies are spectrally indistinct from their surroundings, due to mantling by dust. Where spectral information on gully sediments was obtained, a variety of mineralogies were identified. Their relationship to the source rock suggests that gully‐forming processes transported underl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 55 publications
4
7
0
Order By: Relevance
“…May be proxy for other favorable conditions; thermophysical classes correlate with latitude. Gullies are not routinely associated with hydrated minerals (Núñez et al, 2016). Consistent with no frequent or long-lived water-rock interactions.…”
Section: Discussionmentioning
confidence: 84%
“…May be proxy for other favorable conditions; thermophysical classes correlate with latitude. Gullies are not routinely associated with hydrated minerals (Núñez et al, 2016). Consistent with no frequent or long-lived water-rock interactions.…”
Section: Discussionmentioning
confidence: 84%
“…Harrison et al (2017) found that fans associated with active gullies in Gasa Crater have higher thermal inertia than other gully fans, yet lower thermal inertia than talus slopes. The hysperspectral imaging system CRISM has been used to examine the composition of the materials in and around gullies Stepinski, 2018, 2017;Barnouin-Jha et al, 2008;Núñez et al, 2016a) and suggested that: (1) gullies are hosted on a wide range of geological materials, (2) in some cases gullies expose underlying rock and move it downslope, (3) many other gullies show no spectral difference from their surroundings and (4) there is no systemtic association between hydrated minerals and gullies even in the new light-toned deposits near gullies. Heldmann et al (2010) used CRISM data and also confirmed that recent light-toned deposits in Penticton Crater have no spectral differences to surrounding material.…”
Section: Figure 11mentioning
confidence: 99%
“…Gully growth may be limited by: (a) decreasing geomorphological activity in gullies over time following crater formation [De Haas et al, 2015c], (b) the latitude-dependent mantle acting as a barrier to bedrock-incision and enlargement once established [De Haas et al, 2015c], (c) alternating erosional/depositional episodes driven by orbital cycles [Dickson et al, 2015] or (d) a combination of these factors. Additionally, we know that some gully-fans are fed by alcoves that cut into bedrock [e.g., Johnsson et al, 2014;De Haas et al, 2015c;Núñez et al, 2016] while other gully-fans are fed by alcoves cutting into LDM or glacial deposits [e.g., Head et al, 2008;Conway and Balme, 2014;Núñez et al, 2016], which may be related to the evolution of the host-crater wall over time.…”
Section: Introductionmentioning
confidence: 99%